Prevalence of Insomnia Symptoms in Older Chinese Adults During the COVID-19 Pandemic: A Meta-Analysis - Zhang, Qian-Qian; Li, Lan; Zhong, Bao-Liang (Frontiers in Medicine, 2021)
Background: The ongoing COVID-19 pandemic has disproportionately affected the sleep health of older adults, but the limited number of studies on insomnia symptoms of older Chinese adults differed in terms of screener of insomnia, sample size, and prevalence, making mental health planning for this population difficult. This meta-analysis estimated the prevalence of insomnia symptoms in older Chinese adults during the COVID-19 pandemic. Methods: Both Chinese (CNKI, Wanfang, VIP) and English (PubMed, EmBase, PsycInfo) databases were systematically searched to identify cross-sectional studies containing data on the prevalence of insomnia symptoms in older Chinese adults during the pandemic. Risk of bias (RoB) of included studies was assessed with the Joanna Briggs Institute Critical Appraisal Checklist for Studies Reporting Prevalence Data. Results: Nine studies with a total of 27207 older Chinese adults were included. RoB scores of these studies ranged between zero and six. The pooled prevalence rates of insomnia symptoms and moderate and severe insomnia symptoms were 24.6% (95% confidence interval [CI]: 19.5-30.5%) and 11.1% (95%CI: 7.2-16.9%), respectively. In subgroup analysis, significantly higher prevalence rates were observed in studies defining insomnia symptoms as “Insomnia Severity Index (ISI) ≥ 8” than in those defining them as “ISI ≥ 15” (32.6% vs. 15.6%, P<0.001) and in older adults living in the COVID-19 epicenter than in those living in other places (35.2% vs. 23.3%, P=0.006). Conclusion: Nearly one out of every four older Chinese adults suffered from insomnia symptoms during the pandemic. Mental health services for this population during the pandemic should include supportive activities aimed at improving mental wellbeing, periodic assessment of insomnia symptoms, and psychiatric assessment and treatment when necessary.